The impact of the coexistence of multiple norms from different sources of international law on change to the jus ad bellum - Johnston, KA (2022)
This thesis analyses what would be required as a matter of international law to establish that a change to the jus ad bellum has occurred; that is, that states are permitted to use force in situations where it was previously unlawful under international law, or are prohibited from using force in situations where that conduct was previously lawful. More specifically, this thesis analyses how the international law norms that regulate the use of force may be modified, given that the jus ad bellum comprises multiple international law norms, from different sources of international law, some with distinctive characteristics such as jus cogens status, some of which address the same subject matter, and some of which refer to, limit the scope of, or provide exceptions to each other. It is argued that this coexistence of different kinds of international law norms impacts how those norms are modified, and so will affect how the jus ad bellum can change.